Clima organizacional y su incidencia en el desempeño laboral del GAD de Guano - Keila Geomara, Ayala Paguay (2022)
ABSTRACT This research rescues the importance in the work performance of Ecuadorian public institutions, and in this case study, in the Decentralized Autonomous Government, GAD, in Guano city, the organizational environment dimension. In this way, a diagnostic tool for the organizational environment are designed and implemented, based on leadership, communication, motivation, control, physical condition, decision-making and, communication dimensions. An effective organizational environment contributes to the motivation and improvement of results in the workers. Assuming goals proposed, it is demonstrated the importance of the organizational environment in Guano GAD as a key to productivity and efficiency in public services; diagnose the current state of the organizational climate of the Guano GAD and its impact on productivity and efficiency in public services; analyze the incident variables in the organizational climate of the Guano GAD and influence on job performance; suggest actions that minimize unwanted effects on the organizational environment in Guano GAD, and improve productivity and efficiency in public services. To carry out this research, the hypothetical method is assumed, by expanding the quality of the knowledge formulated from induction, through deduction, in a non-experimental design by not manipulating any variable. Types of research are adopted, exploratory, descriptive, study of analysis, explanatory, and synthesis of information sources, expert judgment method, mathematical-statistical methods, inductive deductive method. Keywords: Organizational climate, Work performance, public institution, motivation, leadership, teamwork, communication